Vehicle collision simulation based on non-classic tire traces. Issue 1 (February 2020) - Śledziński, M; Lewandowski, A
Abstract: In traffic conditions, vehicle collisions often result in tire traces on the road, vehicles and humans. Tire traces on the road can have diverse characteristics. A non-classic form of such traces is the subject of the present analysis. The selected non-typical trace form is characterized by a segmental course with diverse geometric features. The goal of this work is a full analysis of the trace generation mechanism using modern simulation tools. In the paper, the influence of selected vehicle parameters and road surface characteristics on the trace form have been analyzed. Research results indicate the usefulness of PC-Crash software for analyzing road accidents, also in regards to non-typical tire traces.